2021
DOI: 10.1103/physrevlett.127.186001
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Electron Solvation Induced by Bursts of Laser-Accelerated Protons in Liquid Water

Abstract: Understanding the mechanisms of proton energy deposition in matter and subsequent damage formation is fundamental to radiation science. Here we exploit the picosecond (10 −12 s) resolution of laser-driven accelerators to track ultrafast solvation dynamics for electrons due to proton radiolysis in liquid water (H 2 O). Comparing these results with modeling that assumes initial conditions similar to those found in photolysis reveals that solvation time due to protons is extended by > 20 ps. Supported by magnetoh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 50 publications
1
7
0
Order By: Relevance
“…Our experimental observations backed up with combined Monte-Carlo-and particle dynamics simulations revealed that the observed solvation of electrons evolved with a delay of > 20 ps when compared to models developed for electron and x-ray irradiation. 1 This is in agreement with earlier work that studied electron solvation in liquid water post electron irradiation and proposed a higher solvation time relative to x-ray irradiation due to the higher energy density deposited within the medium. 14 Understanding these secondary electron solvation dynamics post proton passage in detail is key to developing accurate models about the complete radiolytic process.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Our experimental observations backed up with combined Monte-Carlo-and particle dynamics simulations revealed that the observed solvation of electrons evolved with a delay of > 20 ps when compared to models developed for electron and x-ray irradiation. 1 This is in agreement with earlier work that studied electron solvation in liquid water post electron irradiation and proposed a higher solvation time relative to x-ray irradiation due to the higher energy density deposited within the medium. 14 Understanding these secondary electron solvation dynamics post proton passage in detail is key to developing accurate models about the complete radiolytic process.…”
Section: Resultssupporting
confidence: 92%
“…In our recent experiments we investigated these interactions by single-shot time-resolved optical streaking of the energy deposition region of laser-accelerated proton bunches in liquid water. 1 The absolute timing reference provided by the x-rays emitted from the laser-plasma-interaction and the sub-ps time resolution revealed that ionized electrons solvate > 20 ps delayed compared to experiments with lower deposited energy density. In this paper we discuss first approaches to explain these observations by micro-dosimetric considerations regarding the background molecules excitation of vibration states and polarization.…”
mentioning
confidence: 98%
“…The probe then enters an imaging spectrometer which spatially separates the frequencies producing an optically streaked image of the spatiotemporal evolution of opacity in the sample. 7,11,12…”
Section: Experimental Methodsmentioning
confidence: 99%
“…With improving parameters of this technique, the number of applications is increasing steadily. As such, the first radio-biological in vivo studies of tumor irradiation with laser-accelerated ions investigating the FLASH effect have been conducted [9] , fundamental ion-matter interactions in high-energy deposition regions have been investigated [10][11][12] and the application of laser-accelerated ion bunches for fuel ignition in inertial confinement fusion has been discussed [13][14][15] . All of these applications require a precise ion spectrum determination for depth-dose verification, model input and cross-section maximization.…”
Section: Introductionmentioning
confidence: 99%
“…Demonstrated by several experiments, this ionoacoustic approach is also capable of detecting mono-energetic bunches of 20 MeV protons down to minimum energy deposition of 10 12 eV, equivalent to a particle number of 5×10 4 with an accuracy in the range verification of ±30 µm [28] . Similarly, 1 H, 238 U, 124 Xe and 12 C ions in excess of hundreds of MeV/u kinetic energies were characterized and applicability up to 1 GeV was proposed [29,30] . Applying multiple transducers, it has been shown that ionoacoustic tomography of the ion beam's Bragg-peak profile is possible in vivo and in real-time, with sub-mm accuracy [31] .…”
Section: Introductionmentioning
confidence: 99%